2017
DOI: 10.1002/cvj.12060
|View full text |Cite
|
Sign up to set email alerts
|

Prayer Type, Disclosure, and Mental Health Across Religious Groups

Abstract: Researchers have found that disclosure to God partially explains associations between certain prayer types and mental health in a Christian sample. Although researchers have discovered several mediators explaining associations between prayer types and mental health, the use of predominantly Christian samples limits generalizability. In this study, the authors tested disclosure to God as a mediator in Jewish, Muslim, and Christian subsamples. Analyses indicated several differences among the groups; disclosure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
(79 reference statements)
2
7
0
Order By: Relevance
“…In the latter, the focus is on awaiting divine wisdom, understanding, or guidance from God, and in the former—on the worship of God, without reference to specific circumstances or needs. The differences in prayer types regarding the presence or quality of communication were considered within the context of Poloma and Pendleton’s ( 1991 ) study of prayer types’ association with mental health (Winkeljohn Black et al 2015 , 2017 ). The aim of this study was to examine whether these differences may affect prayer types’ association with well-being within the Laird et al’s ( 2004 ) conceptualization of prayer.…”
Section: Prayer Typesmentioning
confidence: 99%
See 3 more Smart Citations
“…In the latter, the focus is on awaiting divine wisdom, understanding, or guidance from God, and in the former—on the worship of God, without reference to specific circumstances or needs. The differences in prayer types regarding the presence or quality of communication were considered within the context of Poloma and Pendleton’s ( 1991 ) study of prayer types’ association with mental health (Winkeljohn Black et al 2015 , 2017 ). The aim of this study was to examine whether these differences may affect prayer types’ association with well-being within the Laird et al’s ( 2004 ) conceptualization of prayer.…”
Section: Prayer Typesmentioning
confidence: 99%
“…Also nowadays, many people disclose their problems, for example health concerns to God (VandeCreek et al 2002 ). Winkeljohn Black et al ( 2015 , 2017 ) have begun investigating how prayers may include disclosures with the benefits to the discloser’s mental health in a Christian sample (Winkeljohn Black et al 2015 ), as well as in Jewish and Muslim samples (Winkeljohn Black et al 2017 ). They found that disclosure to God mediated the positive associations between colloquial and meditative prayer and mental health.…”
Section: Disclosure To God As Mechanism In the Association Of Prayer mentioning
confidence: 99%
See 2 more Smart Citations
“…The universality of prayer makes its variation considerable. Different religious traditions, cultural norms, and historical eras produce a vast array of prayer types and meanings (Baesler 2001;Black et al 2015Black et al , 2017Chakraborty 2015;Hammerling 2008). In order to methodically understand this variation, we propose four separate dimensions of the prayer experience.…”
Section: Introductionmentioning
confidence: 99%